Neutrophil elastase from myeloid cells promotes TSC2-null tumor growth. Issue 4 (April 2020) - Taya, Manisha; Garcia-Hernandez, Maria de la Luz; Rangel-Moreno, Javier; Minor, Briaunna; Gibbons, Erin; Hammes, Stephen R
Abstract : Chronic inflammation promotes progression of many cancers, with circulating myeloid-derived suppressor cell (MDSC) levels correlating with poor prognosis. Here we examine effects of MDSCs on lymphangioleiomyomatosis (LAM), a rare disease occurring almost exclusively in women whereby estrogen-sensitive metastatic TSC2-null tumors grow throughout the lungs, markedly reducing pulmonary function. The LAM cell origin remains unknown; however, previous work demonstrated that Tsc2 inactivation in the mouse uterus induced estrogen-dependent myometrial tumors with nearly all features of LAM. Half of these animals developed metastatic myometrial tumors in the lungs, suggesting that LAM cells might originate from the myometrium, possibly explaining its overwhelming female prevalence and estrogen-sensitivity. Here we report that MDSC levels, and in particular granulocytic myeloid cell levels, are elevated in the periphery and in tumors of uterine-specific Tsc2 -null mice. Importantly, MDSC depletion or inhibition of their recruitment impairs myometrial tumor growth. RNA and protein analysis of Tsc2 -null myometrial tumors and xenografts demonstrate high expression and activity of the serine protease neutrophil elastase (NE), with selective qPCR studies indicating a stromal origin of the NE. Notably, treatment with sivelestat, a known NE inhibitor already approved for human use in some countries, reduces tumor growth similar to MDSC depletion. Furthermore, NE promotes Tsc2 -null tumor cell growth, migration, and invasion in vitro . Finally, NE-expressing myeloid cells are present throughout the lungs of LAM patients but not controls. These data suggest that NE derived from granulocytic myeloid cells might directly promote LAM tumor cell progression and could be a novel therapeutic target for LAM.